2017
DOI: 10.1007/s10198-017-0902-x
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence for the performance of generic preference-based measures? A systematic overview of reviews

Abstract: ObjectiveTo assess the evidence on the validity and responsiveness of five commonly used preference-based instruments, the EQ-5D, SF-6D, HUI3, 15D and AQoL, by undertaking a review of reviews.MethodsFour databases were investigated using a strategy refined through a highly sensitive filter for systematic reviews. References were screened and a search for grey literature was performed. Identified citations were scrutinized against pre-defined eligibility criteria and data were extracted using a customized extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 43 publications
(83 reference statements)
0
67
0
Order By: Relevance
“…Lin et al [11] also showed that UA dimension correlated strongly with subscales on the Patient-Reported Outcome Measurement Information System (PROMIS), such as physical function, fatigue, and satisfaction with social roles. It has also been suggested that interpersonal relationships might be important as a bolt-on dimension [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [11] also showed that UA dimension correlated strongly with subscales on the Patient-Reported Outcome Measurement Information System (PROMIS), such as physical function, fatigue, and satisfaction with social roles. It has also been suggested that interpersonal relationships might be important as a bolt-on dimension [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory construct validity and responsiveness were also reported in past systematic reviews of EQ-5D in musculoskeletal [91], schizophrenia [92], skin [93], metabolic [94,95], and respiratory diseases [96]. However, the current finding that EQ-5D is valid and responsive for patients with eye and heart diseases is at odds with the finding from a systematic review [95] that was mainly based on evidence from European populations. The contradictory findings from the two systematic reviews suggest that the measurement properties of PBMs might vary from region to region.…”
Section: Discussionmentioning
confidence: 55%
“…Also, missing data were imputed using multiple imputation by chained equations, which is generally considered the most valid method to account for missing data in economic evaluations [35,36]. Third, while the EQ-5D-3L is generally considered valid for use in COPD populations [26], evidence also exist that the measure might miss important generic and specific items of relevance for COPD populations, among which are breathing [38], cough and dyspnoea [39,40]. Moreover, the EQ-5D-3L was measured at month 1 after randomisation, month 3 and every 3 months thereafter until month 24.…”
Section: Discussionmentioning
confidence: 99%
“…Utility values were obtained using the Dutch version of the EQ-5D-3L with the Dutch tariff [24]. The EQ-5D-3L was chosen as it is the most widely used measure for economic evaluations worldwide [25] and it has been deemed valid for COPD populations [26].…”
Section: Outcome Measuresmentioning
confidence: 99%